STATE-LEVEL APPROACHES TO MANAGING THE USE OF CONTRACEPTIVES IN WILDLIFE IN THE UNITED STATES - Eisemann, John D.; O'Hare, Jeanette R.; Fagerstone, Kathleen A. (DigitalCommons@University of Nebraska - Lincoln, 2013)
Several fertility control agents have recently been registered with the U.S. Environmental Protection Agency for management of wildlife or other free-ranging animals. The registration of GonaConTM Immunocontraceptive Vaccine for use in white-tailed deer (Odocoileus virginianus) and OvoControl for use in Canada geese (Branta canadensis) and pigeons (Columba livia) has caused state wildlife and land management agencies to review their regulatory authority over the use of contraceptives in wildlife. As a result, many states are taking steps to ensure legislation or policies are current with emerging technologies. This article examines the various approaches states are taking to regulate the use of contraceptives. Regardless of the final regulatory approach, biological, social, economic, and political implications must all be discussed as this new tool is introduced into the field of wildlife management. Thoughtful consideration of all aspects of wildlife contraceptive use will lead to the development of sound, best management practices for current and future products.